Diagnostic yield of targeted massively parallel sequencing in children with epileptic encephalopathy. (July 2018) - Kothur, Kavitha; Holman, Katherine; Farnsworth, Elizabeth; Ho, Gladys; Lorentzos, Michelle; Troedson, Christopher; Gupta, Sachin; Webster, Richard; Procopis, Peter G.; Menezes, Manoj P.; Antony, Jayne; Ardern-Holmes, Simone; et al.
Highlights: The EE panel yield is highest in early onset epileptic encephalopathies. Clinical phenotyping is central to the interpretation of genetic results. Genetic diagnosis has specific implications for management in selected cases. Targeted MPS EE panel is economical in avoiding the potential diagnostic odyssey. Abstract: Purpose: To report our institutional experience of targeted massively parallel sequencing (MPS) testing in children with epilepsy. Method: We retrospectively analysed the yield of targeted epileptic encephalopathy (EE) panel of 71 known EE genes in patients with epilepsy of unknown cause, who underwent clinical triage by a group of neurologists prior to the testing. We compared cost of the EE panel approach compared to traditional evaluation in patients with identified pathogenic variants. Results: The yield of pathogenic variants was 28.5% (n = 30/105), highest in early onset EE <3 months including Ohtahara syndrome (52%, n = 10/19) and lowest in generalized epilepsy (0/17). Patients identified with pathogenic variants had earlier onset of seizures (median 3.6 m vs 1.1y, p < 0.001, OR 0.6/year, P < 0.02) compared to those without pathogenic variants. Pathogenic/likely pathogenic variants were found in ALDH7A1 (2), CACNA1A (1), CDKL5 (3), FOXG1 (2), GABRB3 (1), GRIN2A (1), KCNQ2 (4), KCNQ3 (1), PRRT2 (1), SCN1A (6), SCN2A (2), SCN8A (2), SYNGAP1 (1), UBE3A (2) and WWOX (1) genes. This study expands the inheritance pattern caused by KCNQ3 mutations to include an autosomal recessive severe phenotype with neonatal seizures and severe developmental delay. The average cost of etiological evaluation was less with early use of EE panel compared to the traditional investigation approach ($5990 Australian dollars (AUD) vs $13069 AUD ; p = 0.02) among the patients with identified pathogenic variants. Conclusion: Targeted MPS testing is a comprehensive and economical investigation that enables early genetic diagnosis in children with EE. Careful clinical triage and selection of patients with young onset EE may maximize the yield of EE panel testing.